(untitled) (Eurasian Scientific Herald, 2023)
The article provides a comparative analysis of technological competition between the United States, China and the Russian Federation. The study examines the main directions of technological competition between these countries, their technological capabilities, competitive advantages and weaknesses, as well as the impact of technological competition on the global economy and politics. The study found that the U.S. retains its lead in technological competition, but China is rapidly closing that gap. The Russian Federation lags behind the United States and China in the development of some advanced technologies, but has significant advantages in other areas. Technological competition between the United States, China, and Russia will have farreaching consequences for the global economic and political order.